The Role and Function of Leadership in the Private Educational Institution of MI Al-Markaz Al-Islami Maros - Maryam Djasdar; Mardhiah Hasan; Bustan Ramli (al-Afkar, Journal For Islamic Studies, 2026)
Private educational institutions as organizers of educational activities other than public schools, in the management of private educational institutions certainly require leadership that has managerial skills that know their functions and roles in the institution so that they can face all more complex situations with global changes. This article aims to provide knowledge about the context of private educational institution leadership, both in structure, role and function. The research method uses a qualitative method with data collection techniques carried out by carrying out identification first, observation, interviews, documentation and drawing conclusions. Based on the results of the analysis, it is concluded that the role and function of the principal at MI Al-Markaz Al-Islami Maros have been carried out well, so that the learning process can be carried out effectively and efficiently with the hope that educational goals can be realized.